Nonsurgical Endodontik Retreatment of Maxillary First Premolar : A Case Report - Yongki Hadinata W; Karlina Samadi (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background : There are some factors can cause endodontic failure such as inadequate in cleaning or shaping step, non hermetic obturation, or poor restoration, which can cause bacteria multiply. Purpose : To report the management of endodontic failure with nonsurgical treatment. Case : 46-year-old woman came to Airlangga Dental Hospital Conservative Dentistry Department to treat her upper right tooth which show symptomatic pain in the last 2 weeks. The tooth has been treated and crowned with porcelain fused to metal about 10 years ago. Clinical examination show the presence of fistula on premolar buccal gingiva, react to percussion. Radiographic examination show not hermetic obturation in one root canal and radiolucency in the periapical area. The diagnosis for maxillary first premolar is previously treated tooth with chronic periapical abscess.. Treatment : Crown and post was removed from the tooth, and endodontic retreatment was done. Follow up 6 months after the retreatment show no reaction to percussion, and radiographic examination show no enlargement periapical lesion. Conclusion : Nonsurgical endodontic retreatment always become the first choice to resolve endodontic failure for previously treated tooth.